MEDIDA DE COPA PARA DETERMINAÇÃO DA DENSIDADE POPULACIONAL DE CEDRELA FISSILIS - PEREIRA, Lílian Daniel; FLEIG, Frederico Dimas; MEYER, Evandro Alcir; VUADEN, Elisabete; LANZARIN, Karina (Brazilian Journal of Biometrics, 2017)
Cedrela fissilis (Vell.) is potential specie for management in native forests. However, for its proper management, it is necessary to know its behavior in the forest. With this in mind, the aim of this study was obtain information about spacing and number of tree per hectare de Cedrela fisslis (Vell.). The following Information was collected: diameter at breast height and insertion of eight rays of crown emerging C. fissilis. Five models about crown diameter and diameter at breast height (DBH) were tested and, after choosing one, the bottom and upper line of this relation was drawn. The number of trees per hectare (N) was calculated dividing area of hectare by area of canopy. Regression between crown diameter and DBH presented a good fit and allowed to set limits for reliable density for a given C. fissilis diameter. The spacing for obtain C. fissilis with 30 cm in diameter must be between 2 and 8 m, for 40 cm in diameter, between 3 and 10, for 50 cm in diameter, between 4 and 11 and, for 60 cm in diameter, between 6 e 13 cm.